Selective Laser Hardening of Aluminium AA6061-O Alloy with Nanosecond Laser Pulses - Furat I. Hussein; Sanaa Al-Sumaidae; Ahmed Alhamaoy; Kareem N. Salloomi; Muhannad Ahmed Obeidi (Diyala Journal of Engineering Sciences)
Conventional hardening, sometimes, is not economically viable due to consuming additional costs and energy. This makes applying selective hardening on specific regions an attractive alternative for members subjected to local friction and wear. This work is devoted for applying cold working hardening on discrete values on regions of aluminum 6061-O alloy using nanosecond fiber laser of 100 W average power and pulse duration of 81 ns. An exaggerated plasma pressure resulted from ablation a thin coat layer on the metal surface was built in order to cause cold plastic deformation and increase the surface hardness of the alloy. The power density (Pd) and pulse overlap percentage (OV) were employed as working parameters. Due to the sensitivity of aluminium alloys to excessive heating, the criteria of the best outcomes were considered according to the objective of the study in supporting the hardness by strain hardening. The higher attained a significant increase in the hardness associated with less consumed optical energy, the most clean and flawless surface, observed by the high-resolution SEM images, which indicates hardening with cold work. The best hardness value is conducted at a Pd of 4.46 GW/cm2 reaching a hardness of 57.6 HV at an OV of 43% and 53.8 VHD at an OV of 77.3%. The X-Ray diffraction analysis (XRD) revealed a reduction of 56% in grain size compared to the original alloy and increase in the number of dislocations density by 378%.